2020
DOI: 10.1590/0034-7167-2019-0059
|View full text |Cite
|
Sign up to set email alerts
|

Communication of bad news in pediatrics: integrative review

Abstract: Objectives: to identify the scientific evidence of the elements of communication in the process of communicating bad news in pediatrics. Methods: integrative review searched in the LILACS, PubMed and WoS databases. Primary studies in Portuguese, Spanish or English were included. Results: the evidence from the 40 studies were organized according to the elements of communication: sender (family and/or professional), receiver (family and/or child), message (bad or difficult news about diagnosis/prognosis; empat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
13

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 45 publications
1
14
0
13
Order By: Relevance
“…First generation: exchange of knowledge with the team of professionals from a specialized pediatric infectology service who pointed out the problem of monitoring the disclosure of the HIV diagnosis to the child. Production of a prototype (action plan) developed in a participatory manner with professionals in convergent-care research to support the careeducational practice of supporting the family in disclosing to children (14) Second generation: synthesis of scientific evidence from two review studies: an integrative review about the disclosure of bad news in pediatrics (15) and a scope review about the disclosure of the HIV diagnosis in pediatrics (16) Third generation: creating the guide's content • synthesizing and structuring the content according to the elements of the communication framework • discussion of the guide's version with the team of professionals from a specialized pediatric infectology service • evaluation of the guide's content: validation by the experts committee Based on the review studies, the evidence were organized in each communication element (19) . The first session presents the guide, and it aims to show its applicability in care practice and is followed by the other sessions with the following elements: message, manner and communication channel (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…First generation: exchange of knowledge with the team of professionals from a specialized pediatric infectology service who pointed out the problem of monitoring the disclosure of the HIV diagnosis to the child. Production of a prototype (action plan) developed in a participatory manner with professionals in convergent-care research to support the careeducational practice of supporting the family in disclosing to children (14) Second generation: synthesis of scientific evidence from two review studies: an integrative review about the disclosure of bad news in pediatrics (15) and a scope review about the disclosure of the HIV diagnosis in pediatrics (16) Third generation: creating the guide's content • synthesizing and structuring the content according to the elements of the communication framework • discussion of the guide's version with the team of professionals from a specialized pediatric infectology service • evaluation of the guide's content: validation by the experts committee Based on the review studies, the evidence were organized in each communication element (19) . The first session presents the guide, and it aims to show its applicability in care practice and is followed by the other sessions with the following elements: message, manner and communication channel (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…The knowledge synthesis phase (second generation) was developed through two review studies, an integrative one (15) and a scope one (16) . The reviews identified evidence in the national and international scientific literature that supports the disclosure of the HIV diagnosis in pediatrics.…”
Section: Study Protocolmentioning
confidence: 99%
“…No contexto de assistência à criança, há indicação de que a comunicação de notícias difíceis seja feita pelo profissional que acompanha a criança, e quando for de teor técnico, indica-se que seja feita pelo médico, porém, com a presença de outros profissionais envolvidos no cuidado à criança e familiares, pois cada profissão possui atribuição e competências específicas, que somadas compõem uma abordagem completa de atenção à saúde 23 .…”
Section: Discussionunclassified
“…De maneira específica, o/a enfermeiro/a tem distintos papeis no momento da comunicação de notícias difíceis, seja como responsável por transmitir a notícia, acompanhar outro profissional neste momento e manejar junto aos pacientes e/ ou familiares o impacto promovido pela notícia 3,23 . Ressalta-se que é possível que em grande parte das vezes, o papel do/a enfermeiro/a envolve falar com pessoas que já receberam uma notícia difícil, e por isso, as habilidades de comunicação serão necessárias para acessar questões voltadas à dimensão espiritual, esclarecer dúvidas, auxiliar na tomada de decisão e em resoluções necessárias para o contexto de saúde, oferecer apoio, manejar emoções, sentimentos e medos 24 .…”
Section: Discussionunclassified
See 1 more Smart Citation